The use of synthetic colloids in dogs and cats - SAVVAS (Ι. ΣΑΒΒΑΣ), Ι.; PAPASTEFANOU (Α. ΠΑΠΑΣΤΕΦΑΝΟΥ), Α.; ANAGNOSTOU (Τ. ΑΝΑΓΝΩΣΤΟΥ), Τ. (Journal of the Hellenic Veterinary Medical Society, 2018)
It is common in small animal clinical practice to administer fluids in order to replace water deficits or to treat diseases. One of the indications of the fluid therapy is treatment of low intravascular volume, which begins with crystalloid administration. Colloids, however, are more effective in maintaining intravascular volume than crystalloid solutions, because they contain high molecular weight molecules that do not cross capillary walls. As a result, plasma oncotic pressure increases, resulting in water transfer from the interstitial to the intravascular space. The administered volume of a colloid is equal or slightly bigger than the required replacement volume, and the total volume administered is lower than the required volume of a crystalloid. Therefore, colloids should be considered when a patient does not appear to be responding appropriately to the crystalloid fluid infusion or when oedema develops prior to adequate blood volume restoration. The most common side effects of colloid administration may be volume overload, anaphylactic reaction, renal toxicity and coagulation disorders. Colloids are natural and synthetic. Natural colloids include whole blood, plasma and blood products. Synthetic colloids are dextrans, gelatins and starches. Haemoglobine-based oxygen carriers may improve oxygenation and act as colloids. Dextrans have a mean molecular weight of either 40,000 or 70,000 daltons. They have a short half-life and may cause coagulation defeciencies, anaphylactic reactions or acute renal failure. Gelatins have a shorter half-life. Starches are glucose polymers with glycosidic bonds and hydroxyl-ethyl groups. According to the number of these groups, they are distinguished in three types: hetastrach, tetrastarch and pentastarch. They have oncotic effects, long half-life and few side effects. Colloids are mainly administered in shock, as well as in hypoproteinaemia, sepsis and third space losses. They are always co-administered with crystalloids, in order to replace interstitial water as well. Water loss replacement is treated in three phases. Initially, intravascular volume is restored (resuscitation phase), then interstitial space is hydrated (rehydration phase) and finally cells are hydrated (maintenance phase). Depending on the underlying disease, different combinations of crystalloids and colloids are used. Special attention is needed in cases of internal haemorrhage, increased endothelial permeability and hypoproteinaemia.